Práticas tradicionais de preservação do Meio Ambiente e concepções de saúde entre os Magütagü da Comunidade Mecürane – Vila Betânia - Felipe, Roger da Costa (Brasil, 2022)
This work is an ethnography built from the narratives of the Magütagü de Mecürane elders, which also includes the participation of young people, who are concerned with keeping alive the Traditional Practices of Environmental Preservation and Health Concepts among the Magüta. It seeks, in particular, to understand how the conceptions of the Magüta indigenous elders and young people of the Mecürane community are expressed in the speeches and daily practices about the environment, the specific health processes related to the current scenario of the covid19 pandemic. More broadly, it contributes to a study of indigenous ethnology and proposes to serve as a basis for the discussion of health and development projects for the Magüta indigenous population, emphasizing the appreciation and preservation of their culture, their traditional forms of solidarity and leadership, prioritizing the participation of indigenous peoples in the public policies presented to them.